2021
DOI: 10.1016/j.jpeds.2021.01.072
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences and Spanking Have Similar Associations with Early Behavior Problems

Abstract: Objectives To examine whether adverse childhood experiences (ACEs) and physical punishment (ie, spanking) are unique risk factors for behavior problems in early childhood, and whether ACEs moderate the associations of spanking with child behavior problems. Study design We conducted prospective, longitudinal analyses on 2380 families in the Fragile Families and Child Wellbeing Study. Mothers reported outcomes of externalizing and internalizing behavior problems at age 5 years; and the main predictors, ACEs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…Moreover, the Iranian State permits corporal punishment within schools. While the physical punishment of children in schools and by families is sanctioned by many countries, including Australia, South Korea, and the US (Gershoff 2017), many countries, particularly within the Council of Europe, have implemented legislation to prohibit it, reflecting the wealth of research linking corporal punishment to physical aggression and other problematic behavior in children (DCSF 2007;Douglas and Straus 2006;Ma et al 2021;Simons et al 1998). As Douglas and Straus (2006: 312) argue, "a society in which CP [corporal punishment] is prevalent is likely to be a society in which other types of violence are prevalent"; the social contexts in which the physical punishment of children is common are likely to have a greater acceptance of other forms of interpersonal violence.…”
Section: Iran and The United Nations Convention On The Rights Of The ...mentioning
confidence: 99%
“…Moreover, the Iranian State permits corporal punishment within schools. While the physical punishment of children in schools and by families is sanctioned by many countries, including Australia, South Korea, and the US (Gershoff 2017), many countries, particularly within the Council of Europe, have implemented legislation to prohibit it, reflecting the wealth of research linking corporal punishment to physical aggression and other problematic behavior in children (DCSF 2007;Douglas and Straus 2006;Ma et al 2021;Simons et al 1998). As Douglas and Straus (2006: 312) argue, "a society in which CP [corporal punishment] is prevalent is likely to be a society in which other types of violence are prevalent"; the social contexts in which the physical punishment of children is common are likely to have a greater acceptance of other forms of interpersonal violence.…”
Section: Iran and The United Nations Convention On The Rights Of The ...mentioning
confidence: 99%
“…Pētījumi rāda, ka vecāku un bērnu mijiedarbībai un vecāku audzināšanas stiliem ir nozīmīga loma uzvedības problēmu attīstībā. Pārmērīga fiziskā un psiholoģiskā kontrole (fiziski sodi, kaunināšana), autoritārs, visatļaujošs audzināšanas stils vai novārtā pamešana ir saistīta ar augstāku eksternalizētas uzvedības līmeni pirmsskolas un skolas vecumā (Ma, Lee, & Grogan-Kaylor, 2021;McKee et al, 2008;Pinquart, 2017). Negatīva audzinošā uzvedība var ietekmēt bērna eksternalizētu uzvedību arī pēc vairākiem gadiem.…”
Section: Vecāku Audzināšanas Saistība Ar Bērna Uzvedībuunclassified
“…Additional studies have shown that non-physical psychological and emotional punishment can be as harmful as hitting children (Ma et al, 2021;Wang & Kenny, 2014). As a result of these findings, social scientists along with developmental psychologists, pediatricians, and parenting experts have concluded that these physiologic disruptions can persist far into adulthood and lead to lifelong impairments in both mental and physical health and have highlighted the need for legislation to end corporal punishment in homes and schools.…”
Section: Introductionmentioning
confidence: 99%